2008
DOI: 10.1007/s10336-008-0335-5
|View full text |Cite
|
Sign up to set email alerts
|

The Taiwan Firecrest (Regulus goodfellowi) belongs to the Goldcrest assemblage (Regulus regulus s. l.): evidence from mitochondrial DNA and the territorial song of the Regulidae

Abstract: We evaluated the phylogenetic relationships of the Taiwan Firecrest or Flamecrest, Regulus goodfellowi, on the basis of two mitochondrial markers (cytochrome b, 16S rRNA) and territorial song. Genetic samples from eighteen subspecies of all currently accepted crest and kinglet species were available for comparison. In all molecular tree reconstructions it was clearly apparent the Taiwan endemic species was the sister species of all the palearctic Goldcrests (Regulus regulus) from Bayesian inference of phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 70 publications
2
15
0
Order By: Relevance
“…This finding is reasonable because the close geographical setting between South China and Taiwan provides more opportunities for biotic interchange, thus lowering the genetic endemism of the Taiwanese populations (Qu et al., ). In addition, in agreement with previous studies, we recognized Indochina (Chen, Chang, et al., ; Jiang et al., ; Lv et al., ), Japan (Li et al., ; Nishizawa et al., ) and the Palaearctic (Päckert et al., ) as source regions of endemic Taiwanese species (Figure ). Nevertheless, our result revealed that three endemic species ( Myophonus insularis , Megalaima nuchalis , and Arielulus torquatus ) originated from India & Sri Lanka and the Malay Archipelago, which were rarely considered possible source regions (Figure ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is reasonable because the close geographical setting between South China and Taiwan provides more opportunities for biotic interchange, thus lowering the genetic endemism of the Taiwanese populations (Qu et al., ). In addition, in agreement with previous studies, we recognized Indochina (Chen, Chang, et al., ; Jiang et al., ; Lv et al., ), Japan (Li et al., ; Nishizawa et al., ) and the Palaearctic (Päckert et al., ) as source regions of endemic Taiwanese species (Figure ). Nevertheless, our result revealed that three endemic species ( Myophonus insularis , Megalaima nuchalis , and Arielulus torquatus ) originated from India & Sri Lanka and the Malay Archipelago, which were rarely considered possible source regions (Figure ).…”
Section: Discussionsupporting
confidence: 92%
“…Under these scenarios, Taiwan served as a refuge for temperate species contracted from North China during the Quaternary glaciations (Chou et al., ), as indicated by the extant species (e.g. Regulus goodfellowi , Päckert et al., ), as well as the extinct species (e.g. Mammuthus trogontherii and Equus spp., Kawamura, Chang, & Kawamura, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Evolutionary history of Asian Wren-Babblers (Pnoepygidae; modified from Päckert et al (2013), phylogeny based on 3457 bp concatenated cytb, ND2, GAPDH, TGFB and ODC); genetic distances (cytochrome b) indicated between clades; two species pairs occur in elevational parapatry along the southern QTP margin (Himalayas, Indo-Burmese mountains, SW China), the Sino-Himalayan high-elevation species (Pnoepyga albiventer) shows intraspecific differentiation among three separate clades and indicates species status; genetic differentiation is strongly backed by differences in song (sonagrams at the right) lineages have undergone effective shifts in morphological or behavioural traits-that are biologically meaningful in the sense of species recognition and/or reproductive barriers-can be put to test in a multidisciplinary approach including morphological, ecological and behavioural analyses, recently termed ''integrative taxonomy'' (Padial et al 2010;Schlick-Steiner et al 2010). In case of behavioural traits, passerine species having a rather stereotyped territorial song with low intra-and interindividual variation provide optimal model groups, particularly species-poor genera such as kinglets and treecreepers (Päckert et al 2003(Päckert et al , 2009Tietze et al 2008). Two examples from our own team might illustrate this approach.…”
Section: True Rosefinches (Carpodacus): a Palearctic Radiation From Tmentioning
confidence: 99%